2021
DOI: 10.3390/ijms22041741
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs and Immunity: Coding the Immune System with Noncoding Oligonucleotides

Abstract: Long noncoding RNAs (lncRNAs) represent key regulators of gene transcription during the inflammatory response. Recent findings showed lncRNAs to be dysregulated in human diseases, such as inflammatory bowel disease, diabetes, allergies, asthma, and cancer. These noncoding RNAs are crucial for immune mechanism, as they are involved in differentiation, cell migration and in the production of inflammatory mediators through regulating protein–protein interactions or their ability to assemble with RNA and DNA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 153 publications
(172 reference statements)
0
41
0
Order By: Relevance
“…Innate immune cells such as macrophages initiate the inflammatory response by increasing the production of various inflammatory mediators, including proinflammatory cytokines, NO, adhesion molecules, and PGE 2 . A limited inflammatory response is sufficient in a healthy system to prevent the development of a variety of diseases; however, an excessive or defective inflammatory response can lead to the development of serious inflammatory disorders, including autoimmune diseases [10][11][12][13]. Therefore, identifying candidates that can modulate the immune response is an important strategy for the development of drugs targeting various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune cells such as macrophages initiate the inflammatory response by increasing the production of various inflammatory mediators, including proinflammatory cytokines, NO, adhesion molecules, and PGE 2 . A limited inflammatory response is sufficient in a healthy system to prevent the development of a variety of diseases; however, an excessive or defective inflammatory response can lead to the development of serious inflammatory disorders, including autoimmune diseases [10][11][12][13]. Therefore, identifying candidates that can modulate the immune response is an important strategy for the development of drugs targeting various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Immune disorders, which can result from both underactive and overactive immune systems, increase the risk of developing allergies and diseases, such as type 1 diabetes mellitus, rheumatoid arthritis, lupus, psoriasis, and inflammatory bowel disease [11][12]. Therefore, there is an urgent need to identify effective approaches for treating immune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, lnc‐EPS downregulates immune response genes (IRGs) expression by binding to regulatory regions of IFIT2, RSAD2 (radical S‐adenosyl methionine domain containing 2), 2′–5′ oligoadenylate synthetase 1 (OAS1) and some cytokine/chemokine genes such as CXCL10, CCL5 (C‐C motif chemokine ligand 5) and IL‐6. 71 Expression of lnc‐EPS after entry of SeV is suppressed in bone marrow‐derived macrophages to initiate innate immunity cells activity. 72 …”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…LncRNAs can be found in different cellular compartments, from the nucleus to cytoplasm and mitochondria, and even exported from the cell via exosomes. About 30% of lncRNAs are located in the nucleus, where they can interact with transcription factors, chromatin complexes, and heterogenous ribonucleoprotein complexes [73]. Within the cytoplasmic compartment, lncRNAs can be found in many structures and organelles.…”
Section: Intracellular and Extracellular Compartmentalization Of Lncrnasmentioning
confidence: 99%
“…A recent literature survey of Salamini-Montemurri et al, has identified 215 lncRNAs being involved in OCs, of which for 157 there is experimental proof [8]. Apart from initiation, lncRNAs have been associated with many biological processes associated with metastasis [80], such as the immune response [73], radiation response [81], epithelial to mesenchymal transition (EMT) and stemness [82], cell-to-cell communication, and regulation of the microenvironment in which cells reside [77].…”
Section: The Role Of Lncrnas In Various Biological Processes Related To Ovarian Carcinogenesismentioning
confidence: 99%